Local Wisdom as A Foundation for Earthquake Disaster Mitigation Education to Create Disaster Resilient Generations: A Case Study In Lombok Island - Kosim, Kosim; Gunawan, Gunawan; Rokhmat, Joni; Verawati, Ni Nyoman Sri Putu; Busyairi, Ahmad (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
Lombok Island is a region prone to earthquake disasters. To create a disaster-resilient generation, disaster mitigation education needs to be integrated with local wisdom. This study aims to explore the local wisdom in Lombok Island that can serve as a foundation for earthquake disaster mitigation education. The research employs a qualitative approach using case studies conducted in several locations on Lombok Island. Data were collected through literature reviews, field observations, and questionnaires distributed to students. The findings indicate that there is a variety of local wisdom in Lombok Island relevant to earthquake disaster mitigation, categorized into six areas: 1) local wisdom in construction and disaster mitigation, 2) local wisdom in communication and social interaction, 3) local wisdom in leadership and community management, 4) local wisdom in shared values of unity and solidarity, 5) local wisdom in social and religious values, and 6) local wisdom in traditions and customary rituals. This local wisdom can be integrated into disaster mitigation education programs in schools and communities. Through education based on local wisdom, it is expected that a generation with awareness, knowledge, and skills in addressing earthquake disasters can be developed, thereby reducing disaster risks and impacts.